2020
DOI: 10.1002/jbm.a.36877
|View full text |Cite
|
Sign up to set email alerts
|

Development of antibacterial, ciprofloxacin‐eluting biodegradable coatings on Ti6Al7Nb implants to prevent peri‐implant infections

Abstract: Various types of biodegradable polymers containing lactide, glycolide, caprolactone, and trimethylene carbonate units have been used to obtain ciprofloxacin (CFX)enriched coatings developed on the Ti6Al7Nb alloy, intended for short-term therapy.In the first step, the surface of the Ti6Al7Nb alloy was modified, mostly according to sandblasting and anodic oxidation to obtain the TiO 2 layer. Anodizing can be an effective method for preparing TiO 2 coatings with osteoconductive properties. The polymer containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
(29 reference statements)
0
20
0
Order By: Relevance
“…In order to prevent infections, efforts are made to introduce antimicrobial surfaces [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ] including the incorporation of antibiotics [ 26 , 30 ], several antimicrobial agents [ 25 , 28 , 29 , 31 , 33 ], and micro- and nano-patterned surface technologies [ 25 , 27 , 29 , 32 ], which seek to employ antibacterial or anti-encrusting activity, based on features found in nature [ 34 , 35 ]. However, this goal has not been fully achieved yet, considering that bacteria are highly developed beings that adapt quickly to environmental signals (light, temperature, magnetic fields, and oxygen) [ 2 ], changing the constitution of their membrane, changing their surface receptors and gene expression patterns, which is the process by which the hereditary information contained in a gene, such as the DNA sequence, is used to form a functional gene product, such as proteins or RNA [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to prevent infections, efforts are made to introduce antimicrobial surfaces [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ] including the incorporation of antibiotics [ 26 , 30 ], several antimicrobial agents [ 25 , 28 , 29 , 31 , 33 ], and micro- and nano-patterned surface technologies [ 25 , 27 , 29 , 32 ], which seek to employ antibacterial or anti-encrusting activity, based on features found in nature [ 34 , 35 ]. However, this goal has not been fully achieved yet, considering that bacteria are highly developed beings that adapt quickly to environmental signals (light, temperature, magnetic fields, and oxygen) [ 2 ], changing the constitution of their membrane, changing their surface receptors and gene expression patterns, which is the process by which the hereditary information contained in a gene, such as the DNA sequence, is used to form a functional gene product, such as proteins or RNA [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The research carried out by Orchel et al showed that the poly(lactide-co-glycolide) (PLGA) 85:15 copolymer, which has the most segmented structure among the studied materials, turned out to be the best material for chondrocyte culture [ 115 ]. The experiment carried out by Jawroska et al showed that the use of polymers with an appropriate microstructure to cover medical implants enables the controlled release of ciprofloxacin from their surface, thanks to which obtained product has antibacterial properties [ 116 ]. Moreover, the studies carried by Jelonek et al have proven differences in the sirolimus release profiles from the same composition polymer coatings applied to polymer scaffolds of different composition [ 117 ].…”
Section: Biodegradable Polyestersmentioning
confidence: 99%
“…However, PLGA was also successfully used as a coating on other substrates, e.g., on Ti–6Al–4V alloy in the form of a gentamicin-loaded layer intended for prosthetic hips [ 39 ]. PLGA used in our study was synthesized with Zr(acac) 4 initiator (contrary to Sn(oct) 2 in commercially available bioresorbable polyesters) and has been previously presented as a suitable polymer coating for metallic implants [ 39 , 40 , 41 , 42 , 43 ] or as a coating on Parylene C [ 44 ]. The possibility of encapsulating drugs within the layers provides additional advantages like local delivery of the drug, which makes it even more attractive.…”
Section: Introductionmentioning
confidence: 99%